Business Improvement Districts: A Systematic Review of an Urban Governance Model towards City Center Revitalization - Guimarães, Pedro (2021)
For some time, business improvement districts (BIDs) have entered into the discourse and practice of academics and urban planners. This model for town centre revitalization was created in North America, whose success has led to its transfer to a growing number of countries. This evolution highlights the importance of BIDs as an urban planning practice, as well as an object of study for academics interested in new models for intervening in central urban areas. BIDs are public–private partnerships, framed within an entrepreneurial logic of urban management that aims to increase the cities’ competitiveness. In this article, we aim to unfold the main research subjects of the literature focused on BIDs. We develop a systematic review for said endeavor, resorting to the established PRISMA protocol. After the screening and analysis of selected articles, four main research subjects were documented: (i) urban governance; (ii) urban policies: mobility and transfer; (iii) activities/axis of intervention; and (iv) types of BIDs/places of intervention. The selected literature enhances the contradictory nature of BIDs, ranging from the economic revitalization of city centres to the occasional exclusionary stance, in which it is developed. Our analysis also points to the important role of different actors in all stages of the policy transfer and implementation.